Chironomid Diversity in the River Nzoia Basin in Kenya - Khazenzi, J. A.; Wakhisi, J.; Osano, O.; Raburu, P.; Mogere, S. N. (Africa Environmental Review Journal, 2022)
Chironomids belong to the dipteran family Chironomidae, one of the most widely distributed insect groups in the world. Chironomid larvae are found in freshwaters and can withstand polluted waters which makes them suitable for use in evaluation of aquatic ecosystem health. However, there is incomplete taxonomic knowledge of larvae and scarcity of ecological data on local species in Tropical and Southern Hemisphere regions. The study set out to identify the chironomid genera in the River Nzoia Basin in order to contribute to knowledge on the chironomid diversity in Kenya. Larvae were collected from different sections of River Nzoia and River Sosiani, a subwatershed of River Nzoia, between December 2008 and June 2009. The genera of chironomid larvae were identified using morphological characteristics. Results showed a total of five genera of larvae in the basin with Chironomus, being the most abundant. Simpson’s Reciprocal index in the Nzoia basin was 2.13 with the subfamily Chironominae making 96.54 % of all larvae identified. The diversity of chironomids was not high in the study area but the occurrence and abundance of the Chironomus genus at all the sampled areas makes it possible for their use in water quality studies in the region.